Analisis Pengaruh Debt To Equity Ratio (DER), Laba dan Ukuran Perusahaan terhadap Return Saham pada Perusahaan LQ-45 yang Terdaftar di Bursa Efek Indonesia Tahun 2012-2016 - Firdausa Nuzula; Nasiruddin; Indah Dewi Mulyani; Dumadi; Nur Afridah (Universitas Muhadi Setiabudi, 2019)
There is an increase and decrease in the share price of the LQ-45 company listed on the Indonesia Stock Exchange. The share price of the LQ-45 company is experiencing instability. This study aims to analyze the effect of debt to equity ratio (DER) information, profit, and company size on stock returns in LQ-45 companies listed on the Indonesia Stock Exchange for the 2012-2016 period. The variables used in this study are debt to equity ratio (DER), profit and company size as independent variables, stock returns as dependent variables. This study used 25 samples of LQ-45 companies listed on the Indonesia Stock Exchange (IDX). The data used is secondary data, namely financial statements and shares of LQ-45 companies listed on the Indonesia Stock Exchange (IDX), namely DER, profit, company size and stock returns. Samples were selected using the purposive sampling method. The data type used is secondary data. Data analysis using descriptive statistics, classical assumption testing and multiple regression analysis. The results of this study show that the debt to equity ratio has a significant effect on stock returns. Meanwhile, the variable profit and company size did not have a significant effect on stock returns.